2022
DOI: 10.3389/fimmu.2022.839433
|View full text |Cite|
|
Sign up to set email alerts
|

Mind the “Vaccine Fatigue”

Abstract: BackgroundOmicron scares and speculations are gaining momentum. Amid the nonstop debates and discussions about COVID-19 vaccines, the “vaccine fatigue” phenomenon may become more prevalent. However, to date, no research has systematically examined factors that shape people’s vaccine fatigue. To bridge the research gap, this study aims to investigate the antecedents that cause or catalyze people’s vaccine fatigue.MethodsA narrative literature review was conducted in PubMed, Scopus, and PsycINFO to identify fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 57 publications
0
39
0
Order By: Relevance
“…Another possible explanation for decreased influenza vaccine uptake may be related to vaccine fatigue during the COVID-19 pandemic. Vaccine fatigue, defined as a person’s inaction toward vaccine information or instruction from perceived burden or burnout, [20] can be due to multiple factors, including vaccine side effects, misconceptions about the severity of an infection and need for vaccination, and lack of trust in policymakers. This phenomenon affects the general public, caregivers, and healthcare workers.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation for decreased influenza vaccine uptake may be related to vaccine fatigue during the COVID-19 pandemic. Vaccine fatigue, defined as a person’s inaction toward vaccine information or instruction from perceived burden or burnout, [20] can be due to multiple factors, including vaccine side effects, misconceptions about the severity of an infection and need for vaccination, and lack of trust in policymakers. This phenomenon affects the general public, caregivers, and healthcare workers.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the current research findings, we expected a positive relationship of COVID-19 BVS with (i) FCV-19S ( 49 ), (ii) presence of chronic illnesses ( 50 ), and (iii) support for living with the pandemic, i.e., by reducing the social distancing measures ( 51 ). Research shows that burnout level may influence people's inertia or inaction toward vaccination ( 52 ). A negative association between the COVID-19 BVS and the status of COVID-19 vaccination ( 53 ) was expected.…”
Section: Methodsmentioning
confidence: 99%
“…Many people are becoming weary and frustrated by the rise of breakthrough infections and the notion that there is no foreseeable 'end in sight' for COVID-19 vaccinations as the virus continues to mutate and evade neutralizing antibodies. This apathy and indifference is being referred to as 'vaccination fatigue', which is the inertia or inaction of a person towards vaccine information or instruction due to both burden and burnout [11]. One study from Su et al (2022) found that 'vaccine fatigue' has been observed in the public, children's parents, policymakers, and healthcare professionals and is predominantly driven by the vaccination frequency being recommended by public health authorities, vaccine side effects, disease severity, and a lack of trust in the government and media [11].…”
Section: Vaccination Fatiguementioning
confidence: 99%